The Effect of Raw Material Quality and Production Process on Tobacco Product Quality at KOPA Tarutama Nusantara Jember - Indah, Indah Lestari Wahyu; Suryadinata, Ningrum (Universitas Muhammadiyah Jember, 2024)
This study aims to determine the quality of raw materials and production processes against the quality of tobacco products at KOPA Tarutama Nusantara. This study used an associative quantitative approach, with 50 freelancers as respondents. This study used questionnaires as research instruments. This research also uses validity and reliability tests to test the quality of instruments. The analysis method used is multiple linear regression with the help of SPSS 26 software. The results of this study show that the results of the r square determination test of 49.9% of product quality can be explained by the quality variables of raw materials and production processes, while for the remaining 52.2% explained by other independent variables. Meanwhile, the results of the hypothesis test state that the variable quality of raw materials has a positive and significant effect on product quality. Production process variables are also stated to have a positive and significant effect on product quality.